We Three - Morris, Gouverneur, 1876-1953; Hutt, Henry, 1875-1950 (Salt Lake City, UT : Project Gutenberg, 2007)
"We Three" by Gouverneur Morris is a novel written in the early 20th century. The story revolves around the intertwined lives of Archibald "Archie" Mannering, his friend John Fulton, and John's wife Lucy. The narrative delves into themes of love, friendship, and the societal expectations that accompany their upper-class status, exploring how these dynamics shift across different settings and moments in their lives. At the start of the novel, the protagonist, Archie, shares his unconventional relationship with his friends, effectively foreshadowing the complexities that will unfold. The opening chapters establish a sense of nostalgia and humor as Archie reflects on his upbringing, his connection to the Fultons, and the society they navigate. He alludes to the challenges in his own life and the lives of those around him, particularly highlighting his fondness and concern for Lucy, who is portrayed as both charming and carefree. As the story unfolds, there is a brewing sense of tension between personal desires and social obligations, setting the stage for the deeper explorations of love, fidelity, and self-identity that are likely to follow. (This is an automatically generated summary.)
Release date is 2007-06-21
Produced by Al Haines
Keywords: Married people -- Fiction; Triangles (Interpersonal relations) -- Fiction; United States -- Social life and customs -- 20th century -- Fiction